(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2016)
If it is true that a painting can ‘think visually’, then Diderot was the first one to state it; he also said it better than anyone else. Diderot’s Salons show precisely that the ‘imaginal’ sense that arises from the fruition of pictures needs to be investigated on the basis of the concepts of ékphrasis and theatricality – understood as the capacity of exploring the power of pictures in close relation to the composition of the scene, the expressive and pantomimic gestures and what can be called a ‘theory of affections’.